Large ovarian cystadenofibroma causing large bowel obstruction in a patient with Klippel–Feil syndrome—A case report. (2016) - Mechera, Robert; Menter, Thomas; Oertli, Daniel; Hoffmann, Henry
Highlights: MR imaging may help to determine origin and dignity before surgery. Explorative laparotomy is the appropriate surgical approach for masses of unclear origin and dignity. Intraoperative frozen-sections can avoid extensive fertility impairing surgery. Interdisciplinary management is mandatory in patients with Klippel–Feil syndrome. Abstract: Introduction: Ovarian cystadenofibromas (CAF) are epithelial tumors, which are fairly rare, mainly benign and asymptomatic. The Klippel–Feil syndrome (KFS) is a rare congenital anomaly which combines osseous and visceral development disorders. While bowel obstruction is a common complication in advanced ovarian cancer this condition is rarely described in cystic lesions such as CAF. We report the first case of large bowel obstruction due to a large benign ovarian CAF with an underlying KFS. Presentation of case: A 60-year-old women with a KFS was admitted to the hospital with increasing abdominal girth and bowel obstruction. A CT scan revealed a massive intraabdominal cystic tumor of unclear origin, causing compression of the sigmoid colon with consecutive dilatation of the ascending colon and the small bowel. After successful conservative ileus treatment including nasogastric tube and iv fluids for a few days, we performed an explorative laparotomy, revealing a large cystic tumor originating from the left adnexe. After its removal including left adnexectomy, histological findings confirmed a benign cystadenofibroma. The hospital stay was uneventful and bowel obstruction symptoms resolved immediately. Discussion: Beside careful history taking and physical examination, diagnostic imaging is important to identify CAF. However, the distinction between benign and malignant lesions remains difficult even using MRI. Considering optimal preparation of the patient with successful ileus treatment, laparoscopy may have been the surgical approach of choice. Though, direct laparotomy seemed to be the appropriate approach, considering the unclear origin and dignity of the lesion. Considering the KFS and its inherent malformations interdisciplinary cooperation seems important in such rare cases. Conclusion: Preoperative MR imaging and intraoperative frozen-sections can be helpful to determine the dignity of the neoplasm and avoid fertility impairing adnexectomy in young woman. Interdisciplinary management of such rare conditions seems of utmost importance.